Dietary Glutamic Acid, Obesity, and Depressive Symptoms in Patients With Schizophrenia - Kumar, Pooja; Kraal, A. Zarina; Prawdzik, Andreas M.; Ringold, Allison E.; Ellingrod, Vicki (Frontiers in Psychiatry, 2021)
Introduction: Schizophrenia is a lifelong condition associated with several comorbid conditions such as physical illnesses like obesity, as well as co-occurring psychiatric symptoms such as depression. Research regarding susceptibility to some of these comorbidities has primary focused on genetic risks or neurotransmitters and very little work has been done to understand environmental factors such as diet. In particular, understanding the role of dietary glutamic acid consumption on co-morbidities in patients with schizophrenia is important, as evidence suggests that glutamic acid consumption may directly influence glutamatergic neurotransmission; a key neurotransmitter related to schizophrenia, its associated co-morbidities, and depression. Therefore, the aim of this study was to examine the potential relationship between dietary glutamic acid and depressive symptomatology in patients with schizophrenia, stratified by obesity status, due to its relationship with inflammation, antipsychotic use, and depressive symptoms. Methods: Subjects included in this analysis, were part of a parent cross-sectional study in which included three dietary recalls analyzed using protocols outlined as part of the National Health and Nutrition Examination Surveys (NHANES) standardized criteria. Additionally, body mass index (BMI), and Beck Depression Inventory were obtained at this visit. Subjects with a BMI ≥ 30 kg/m2 were included in the obesity group, and the relationship between glutamic acid consumption and BDI scores was analyzed after controlling for age, race, sex, antidepressant and antipsychotic use, and animal and vegetable protein intake which provide natural forms of dietary glutamic acid. Results: A total of 168 participants were included in this study, of which 42.5% were female and 52.9% were White. The mean BMI for the group as a whole was 33.5 ± 8.7 (kg/m2) and the mean BDI was 14.5 ± 10.2 (range 2–50). No differences were found between obesity groups, other than a greater hyperlipidemia, hypertension, and lower waist to hip ratio. Overall, no relationship was found between dietary glutamic acid and BDI scores, However, for non-obese participants, diets higher levels of glutamic acid were associated with greater depression symptomatology (p = 0.021). Conclusion: These preliminary results indicate a possible correlation between dietary glutamic acid a depressive symptoms in non-obese patients with schizophrenia, although further research is needed to specifically examine this relationship.